Automated stringed robotechnical complex as a prospective method for monitoring of objects’safety and state border areas - D. V. Нansetski (Системный анализ и прикладная информатика)
An innovative project to create a prototype of a multifunctional mobile automated stringed robotic complex is announced. A distinctive feature of the project is the mobility in relocation and the maximum use of artificial intelligence to solve problems of ensuring the security of a protected object or territory.